Cash Recycling Machine (CRM) & its impact on customer satisfaction: A study on UCB PLC - Tanha, Moutusi; Siddique, Maliha Ahmed; Sumon, Md. Monirul Islam; Nurulhoque, Md.; Sazin, Rawshan; Hossain, Peas (Annals of Management and Organization Research, 2023)
Purpose: The primary purpose of this research is to explore Cash Recycling Machine (CRM) systems and determine customer satisfaction after using CRM services. Research Methodology: To collect data for this research, a questionnaire was created and a survey was conducted to assess user contentment with the Cash Recycling Machine (CRM) of the United Commercial Bank (UCB) PLC. During the investigation of the Cash Recycling Machine (CRM) system, a secondary data source was utilized. Results: An analysis indicates that Almost 97% of respondents regularly utilized CRM services while continuing to depend on conventional banking methods. Nevertheless, a significant proportion of participants (over 20%) frequently employed CRM systems. Specifically, 47% utilize these systems four to seven times each month. This study demonstrates that banks are implementing novel services to entice a larger clientele, while consumers are allowed to utilize the banks' fundamental services, such as making deposits and withdrawals. Limitations: Banks are restricted from accessing crucial information owing to data privacy concerns.  Furthermore, the use of secondary data may not adequately reflect the perspective of UCB PLC, owing to scalability issues. Ultimately, the limited sample size is a result of clients' strong unwillingness to allocate time for research. Contribution: This study and its implications can be used for additional research in emerging economies to comprehensively examine the adoption of new technologies in the banking industry. Novelty: The core reaction of consumers to an emerging technology for rapid economic growth.